THE PRONUNCIATION ERRORS MADE BY STUDENTS OF FIRST GRADE OF SENIOR HIGH SCHOOL FRATER MAKASSAR - Ryan Agung Kurnia; Baso Jabu; Munir (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2023)
This study aims to find out what sounds are wrongly spoken by students and the classification that causes pronunciation errors made by students. The method used in this research is descriptive qualitative with a sample of class X IPA 1 which consists of 20 students in one class and uses the cluster random sampling technique. In obtaining the data, the researcher used a reading test and documentation (recording) as an instrument. The results found that pronunciation errors made by students amounted to 22 sound errors such as in sounds (e), (i), (i:), (l), (s), (k), (a), (p), ( ), (r), (h), (t), (ɡ) (z), (ʊ), (n), (ʌ), (f), (d), (c), (ͻ:) and (_), then in the classification of the causes of student pronunciation errors there are 5 such as mother tongue, phonological interference, avoidance, interlanguage transfer, and native language. So it can be concluded that the pronunciation errors made by students are quite large, the errors are caused by their first language so that students often change the meaning, in this case, it is necessary to have extra practice for students in communicating and learning English so that there are no pronunciation errors so that in the future students can be better than before.